Moldo-Romanian trade with agri-food products: Retrospective and perspectives - Alexandru Stratan; Eugenia Lucasenco; Sergiu Tirigan (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
The paper aims to present the trade relations with agri-food products between the Republic of Moldova and Romania during the period 2000 - 2018. Being neighbouring countries, connected not only through the existing border, but also through common historical aspect, the trade with agri-food products is of particular importance for both of countries. Analysis of the trade is carried out by product types, presented in 3 periods: 2000 - 2006, 2007 - 2014 when Romania became an EU member state and 2015 - 2018, after entering into force of DCFTA. Research methods are based on statistical analysis, using the data provided by the National Bureau of Statistics of the Republic of Moldova and UN Comtrade database and Ministry of Economy and Infrastructure of the Republic of Moldova. Overall, there is a growing trend in export and import increase between the countries, while Romania continues to be the top-partner for Moldovanexport of agri-food products. The paper suggests further proposals for cooperation between the countries, with a focus on increasing export values by the both sides.
Keywords: Q17; 330; trade; agri-food products; Republic of Moldova; Romania; European Union